Occupational exposure to metals among battery recyclers in France: Biomonitoring and external dose measurements. (1st August 2022) - Hanser, Ogier; Melczer, Mathieu; Martin Remy, Aurélie; Ndaw, Sophie
Graphical abstract: Highlights: Battery-recyclers were exposed to a mixture of metals: Cd, Co, Cr, Li, Mn, Ni, Pb. Administrative and Sorting workers were the less exposed. Treatment and Maintenance workers were highly exposed (airborne and urinary samples). Urinary samples showed high Cd and Co exposures. Collective preventive measures should be improved: capture at source, containment. Abstract: In battery-recycling facilities, exposure to trace elements may occur through inhalation of contaminated dust or vapor emanating from the treatment processes. Exposure of battery-recycling workers to lead has been quite well covered in the literature. In contrast, we lack data on exposure to other elements contained in batteries. The aim of this study was to characterize the exposure of French battery recyclers to multiple elements using biomonitoring and airborne measurements. Eighty-six workers participated in the study. Inhalable metal concentrations were determined for personal airborne samples, and total exposure was determined from pre-shift and post-shift urine samples collected during the working week. In both types of sample, a total of 33 trace elements were measured using inductively coupled plasma mass spectrometry. Results showed battery recyclers to be mostly exposed to Cd, Co, Cr, Li, Mn, Ni, and Pb. Administrative and sorting workers were exposed at lower levels than maintenance, treatment, and dismantling workers. Cd, Co, Li, Mn, and Ni were detected at high levels in air samples, especially near the treatment facilities, with airborne cadmium levels of up to 79.4 µg/m 3 . Urinary sample analysis indicated exposure to Cd and Co, with levels measured at up to 27.6 and 3.34 µg/g of creatinine, respectively. Concentrations were compared to data reported for e-waste recycling companies. The data presented provide valuable information on exposure to trace elements for workers involved in battery-recycling. They also highlight the need to improve both collective and individual protective measures, which were not sufficient in the participating companies.